Intellectual capital and electronic rights management - Wigger, U. (International Journal of Computer Science in Sport, 2002)
Members and students of any university produce a wealth of new research results, insights and scientifically validated knowledge. Also, in the area of sports informatics, new models and procedures for visual representations and large amounts of simulation models are continuously being developed. Today, modern technologies offer ways to assure optimal use and distribution of such intellectual assets.